Geowissenschaftliche Polarforschung in Deutschland – globale Bedeutung und Perspektiven – - Melles, Martin; Diekmann, Bernhard; Estrada, Solveig; Gaedicke, Christoph; Gohl, Karsten; Jokat, Wilfried; Lembke-Jene, Lester; Läufer, Andreas; Lisker, Frank; Piepjohn, Karsten; Scheinert, Mirko; Schirrmeister, Lutz; et al. (Alfred Wegener Institute for Polar and Marine Research & German Society of Polar Research, 2015)
Polar geoscientific research in Germany during the past decades has substantially contributed to the understanding of the geological structure and history of the polar regions, and of the complex feedback mechanisms operating both in Antarctica and in the Arctic. Important questions could be answered, new ones raised from the results obtained. This strategy paper describes the status quo of Germany‘s polar research in the light of its present social importance. On this basis, the key questions concerning the geological settings and the role of the polar regions in the global climate system are intro- duced, which have to be answered in order to better predict future changes and feedbacks in the Earth System. The results could provide significant support towards a sustainable development of the polar regions. Finally, the need for action for the national polar geoscientific research is outlined with a perspec- tive of 10 to 20 years, based upon the currently existing political and logistical boundary conditions.